TINGKAT KELANGSUNGAN HIDUP DAN KINERJA PERTUMBUHAN IKAN SELINCAH (Belontia Hasselti) DENGAN pH BERBEDA - Novia hasanah (Jurnal Akuakultur Rawa Indonesia, 2019)
ABSTRACT This study aims to evaluate the effect of pH on growth performance and sustainability of Selincah fish, and to test the optimal pH range that can trigger the best growth performance of Selincah fish. The research method used is single RAL. The results showed that treatment with different pH had no significant effect on survival rate, feed conversion, growth of absolute weight, absolute length and daily growth rate of Selincah fish (P>0,05). The optimal pH range that can trigger the best growth performance of Selincah fish is pH 7,0- 7,5 with average value of absolute weight equal to 10,76 gram and average survival value equal to 87,5 %. Keywords : Survival Rate, Growth, pH, Selincah fish.